IMPLEMENTATION OF RELIGIOUS MODERATION EDUCATION FOR SANTRI AT THE MIFTAHUL ULUM SUREN ISLAMIC BOARDING SCHOOL KALISAT JEMBER EAST JAVA - Mustari Bosra; Umiarso Umiarso (Al-Qalam, 2021)
Today's religious moderation is an interesting topic in the interaction and relations of modern society. The emergence of a group or individual actions that are intolerant and disrespectful of other people or groups in physical or verbal treatment is a serious problem in religious moderation. This study aims to explain and describe the implementation of religious moderation education in Islamic boarding school Miftahul Ulum Suren Jember which has a positive influence in forming a safe, dynamic, and conducive community structure. The type of this research was qualitative with a phenomenological approach. The participants in this study were 7 people including clerics and students who meet the predetermined research criteria. Data were collected through interviews and observations using interview and observation instruments. The data analysis technique used in this research was the reduction, presentation, and interpretation of the data. The study’s findings showed that in the implementation of religious moderation education at the Miftahul Ulum Islamic boarding school, there are two important themes which are the concept of religious moderation education and the obstacles and supports in its application. The value of mutual respect and tolerance is the main concept that is taught. Group fanaticism and culturing of figures are negative values that need to be eliminated in religious moderation education. Constraints and obstacles in applying religious moderation education in Islamic boarding schools include the regeneration of Kiai who have equal knowledge to continue the existence of the pesantren. The implication of this religious moderation education has a positive impact in constructing the society’s knowledge and culture. This research still has many limitations both in terms of themes and studies and research implementation techniques. In the future, further research can enrich and strengthen the results of this previous research.